Combating stem and leaf rust of wheat: Historical perspective, impacts, and lessons learned - Dubin, H. J.; Brennan, John P. (International Food Policy Research Institute, 2009)
This case study explores the half century of successful efforts of the international wheat stem and leaf rust resistance programs within the context of the international agricultural research system. The study uses a historical perspective to examine the major factors that underpin the success, and presents the impacts on economic returns, food security, and poverty in developing countries. It concludes that the major reasons for success in research on durable stem and leaf rust resistance rested on the following: symbiotic relationships of the collaborative international and national programs; free exchange of genetic resources and information; human resource development; and long-term donor commitment. Data presented show that the use of durable rust resistance has significant economic returns as well as positive impacts on poverty reduction, nutrition, food security, and the environment. Nevertheless, in recent years, decreased donor support for agriculture and productivity has had negative effects. The recent occurrence of a new strain of stem rust that defeated key durable resistance genes has endangered large wheat areas in developing countries. This highlights the critical need for continuous research and vigilance to keep ahead of the ever changing pathogenic microbes.